Multilevel approach to organizational and group safety climate and safety performance: co-workers as the missing link - Brondino, M.; Pasini, M; Silva, S.A. (Safety Science, 2012)
The aim of this study is to test a model on the relationships between organizational and group safety climate and safety performance, that highlights the importance of co-workers as a safety climate agent side by side supervisors at group level. The idea is to consider the co-workers' safety climate as a necessary part of a multilevel model of safety climates' framework associated to safety performance. Firstly, the assessment of the safety climates' framework which consider organizationa:. safety climate and at group level supervisor's and co-workers' safety climate was performed. Then, the mediating role of co-workers' safety climate between organizational and supervisor's safety climate, and worker's safety behaviours was explored. From the literature, the importance to study safety climate in a multilevel perspective by a theoretical and methodological point of view is known. For these reasons the proposed models were tested with multilevel structural equation modelling. We used a two-level design which considered the individual level and the work-group level. Data collection involved 991 blue-zollars, belonging to 91 work groups, from five Italian manufacturing companies. The research highlighted the importance of considering at group level not only climate referred to supervisor, but also climate ate referred to co-workers. Furthermore, results confirmed the mediating role of co-workers' safety climate and revealed that co-workers' safety climate had a stronger influence on safety behaviours, and in particular on safety participation, than supervisor's safety climate, at individual level as well at group level.